Pengaruh Kepemimpinan Adaptif Di Era Digital Dalam Usaha Membangun Budaya Positif Untuk Tim yang Tangguh - Rofiyana, M.; Aziz, Abdul; Rifqi, Rifqi; Salma, Salma; Salwa, Alya (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the influence of a leader's democratic leadership style in building a positive culture in a team so that it is able to produce a team that is strong and ready to carry out every task. Data collection methods were carried out using internet searching, interviews and observations. The results of the research conducted reveal that the right leadership style is able to influence every individual's behavior in an organization so that adaptive leadership is something that should be implemented by every leader, especially in the digital era where any desired information can be obtained easily. An effective and efficient leadership style can increase the sustainability of employees and the Company, this is because HR is one of the important factors that can influence the sustainability of the Company.